ANALISIS MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN LITERASI DIGITAL SISWA DI SDN JATIROKE II - Amar Amar; Slamet Widodo (Journal of Professional Elementary Education, 2022)
During the COVID-19 pandemic, learning activities have changed, now learning is done boldly. These learning changes reduce literacy interest in students, one of which is SDN Jatiroke II students who experience a decrease in literacy interest. The development of digital technology at this time is very effective in increasing student literacy interest during the pandemic. To increase student literacy interest, schools to improve facilities and infrastructure in the field of literature that follow technological developments at this time by using online media such as online libraries to attract student literacy interest. The purpose of this study is to analyze management facilities and infrastructure as supporting tools to increase student literacy interest during the covid 19 pandemic. This study uses a qualitative method that is a literature study using journals and other literature as the main object. The type of research used is qualitative, namely research that produces information in the form of notes and descriptive data contained in the text under study. The location of the research was at SDN Jatiroke II, Jatinangor District. The results of the study show that facilities and infrastructure services can support digital literacy effectively to increase student literacy interest during the learning period of the covid 19 pandemic